2005
DOI: 10.1017/s1462399405008963
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tendon pathology: molecular basis and therapeutic implications

Abstract: Tendons are frequently affected by chronic pain or rupture. Many causative factors have been implicated in the pathology, which until relatively recently was under-researched and poorly understood. There is now a greater knowledge of the molecular basis of tendon disease. Most tendon pathology (tendinopathy) is associated with degeneration, which is thought to be an active, cell-mediated process involving increased turnover and remodelling of the tendon extracellular matrix. Degradation of the tendon matrix is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 184 publications
(68 reference statements)
4
93
0
2
Order By: Relevance
“…Our results showed that collagenase injection exhibited many key features of tendinopathy including hypercellularity, loss of matrix organization, increased vascularity, and absence of infiltration of inflammatory cells as reported in previous studies (Jarvinen et al 1997;Khan et al 1999;Riley 2005;Fu et al 2002aFu et al , b,2007. The patellar tendon failed to heal histologically by the end of week 32.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that collagenase injection exhibited many key features of tendinopathy including hypercellularity, loss of matrix organization, increased vascularity, and absence of infiltration of inflammatory cells as reported in previous studies (Jarvinen et al 1997;Khan et al 1999;Riley 2005;Fu et al 2002aFu et al , b,2007. The patellar tendon failed to heal histologically by the end of week 32.…”
Section: Discussionsupporting
confidence: 88%
“…13 Most tendon injuries involve a degenerative component that can take years to develop. 71,72 Tendon degeneration, or tendinosis, can lead to matrix disorganization, mucoid degeneration, and fatty infiltration. [73][74][75][76] The hypovascular and bFGF, basic fibroblast growth factor; ACL, anterior cruciate ligament; MCL, medial collateral ligament; PT, patellar tendon; GDF, growth and differentiation factor; IGF, insulin-like growth factor; MSC, mesenchymal stem cell; TGFb, transforming growth factor b; PDGF, plateletderived growth factor; VEGF, vascular endothelial growth factor; SDF-1, stromal cell-derived factor-1.…”
Section: Tendon Injury and Repairmentioning
confidence: 99%
“…There is an emerging hypothesis that excessive mechanical strain on tendons modulates the metabolism and/or phenotype of the resident tenocytes, disrupting the balance of matrix synthesis and degradation (for review, see ref. 15). Partial tendon tearing then occurs through abnormal tissue, and this results in increased strain on the remaining tendon and further deterioration.…”
mentioning
confidence: 99%